Native American religion - Martin, Joel W., 1956- (New York : Oxford University Press, 1999)
Discusses the world view and beliefs of various Native American religions and their role in promoting survival of the devastation caused by the arrival of Europeans.
Includes bibliographical references (p. 151-153) and index.
Keywords: Indians of North America -- Religion -- Juvenile literature; Indians of North America -- Religion